1998
DOI: 10.1530/eje.0.1380401
|View full text |Cite
|
Sign up to set email alerts
|

GH dependence and GH withdrawal syndrome in GH treatment of short normal children: evidence from growth and cardiac output

Abstract: The child's age is a significant determinant of the outcome of GH therapy; prepubertal children respond better on both short term and long term growth, whereas adolescents tend to accelerate their bone maturation more than growth. The present study was designed to evaluate the efficacy of an interrupted GH therapy protocol of young, short normal children. GH was given for a period of 3 years, or until they reached the 25th percentile, then discontinued at a young age (not more than 9 years), and then the child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
(26 reference statements)
0
9
1
Order By: Relevance
“…In addition, we could not confirm the negative effect of discontinuing GH treatment on left ventricular dimensions, as was reported in short normal children [20]. …”
Section: Discussioncontrasting
confidence: 68%
“…In addition, we could not confirm the negative effect of discontinuing GH treatment on left ventricular dimensions, as was reported in short normal children [20]. …”
Section: Discussioncontrasting
confidence: 68%
“…It would seem more straightforward to initiate treatment at the age of 10-11 years and to continue for 3-4 years. Initiation of GH treatment at a younger age, and its termination before final height has been attained, may introduce catch down growth after withdrawal of therapy, as shown for children with idiopathic short stature (23).…”
Section: Discussionmentioning
confidence: 99%
“…found no difference in LV diameter during 2 years of GH treatment (dose 33 μg/kg/day). However, 6 months after cessation of treatment, both LV diameter and cardiac output were reduced compared with baseline . In another study, Daubeney et al .…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, it has been shown that the actual dose given should be individualized to optimize the growth response for all individuals . From the cardiovascular perspective, short‐ and medium‐term GH treatment has been shown to be without negative effects in children with GHD and ISS . Several studies have focussed on the impact of GH therapy on the structure and function of the heart; however, most studies have included only a limited number of children with either GHD or ISS and the given dose of GH has not been individualized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation